Proliferation of primary human hepatocytes and prevention of hepatitis B virus reinfection efficiently deplete nuclear cccDNA in vivo - Allweiss, Lena; Urban, Stephan (Gut, 2017)
OBJECTIVE: The stability of the covalently closed circular DNA (cccDNA) in nuclei of non-dividing hepatocytes represents a key determinant of HBV persistence. Contrarily, studies with animal hepadnaviruses indicated that hepatocyte turnover can reduce cccDNA loads but knowledge on the proliferative capacity of HBV-infected primary human hepatocytes (PHHs) in vivo and the fate of cccDNA in dividing PHHs is still lacking. This study aimed to determine the impact of human hepatocyte division on cccDNA stability in vivo. METHODS: PHH proliferation was triggered by serially transplanting hepatocytes from HBV-infected humanised mice into naïve recipients. Cell proliferation and virological changes were assessed by quantitative PCR, immunofluorescence and RNA in situ hybridisation. Viral integrations were analysed by gel separation and deep sequencing. RESULTS: PHH proliferation strongly reduced all infection markers, including cccDNA (median 2.4 log/PHH). Remarkably, cell division appeared to cause cccDNA dilution among daughter cells and intrahepatic cccDNA loss. Nevertheless, HBV survived in sporadic non-proliferating human hepatocytes, so that virological markers rebounded as hepatocyte expansion relented. This was due to reinfection of quiescent PHHs since treatment with the entry inhibitor myrcludex-B or nucleoside analogues blocked viral spread and intrahepatic cccDNA accumulation. Viral integrations were detected both in donors and recipient mice but did not appear to contribute to antigen production. CONCLUSIONS: We demonstrate that human hepatocyte division even without involvement of cytolytic mechanisms triggers substantial cccDNA loss. This process may be fundamental to resolve self-limiting acute infection and should be considered in future therapeutic interventions along with entry inhibition strategies.